Melengkapi Analisa Teori Akses dengan Pendekatan Kolaboratif pada Konteks Program Perhutanan Sosial: Studi Kasus Lembaga Masyarakat Desa Hutan (LMDH) Rawa Sakti, Pemalang - Dicky Rachmawan; Francisia Saveria Sika Ery Seda; Robert Siburian (Universitas Gadjah Mada, 2021)
The shift of the forest management paradigm in Indonesia in this recent time has given more space for people that align with the Indonesian Government to elevate well-being at once to conserve forest through Social Forestry Program. One model group from 6.411 forest communities that manage forest is Forest Village Communuty or Lembaga Masyaraakat Desa Hutan (LMDH) of Rawa Sakti. This paper aims to describe the structure-process of social forestry program implementation in LMDH Rawa Sakti which uses access theory that is complemented by the collaborative approach. The qualitative approach with descriptive analysis in the case study is conducted through depth interviews (consist of the management and members of LMDH Rawa Sakti, middleman, village officer, and coffee entrepreneur), observation, and focus group discussion. The result shows that negotiation and social relation access is the essential access that can influence five other forms of SRAM by Theory of Access that need to be examined by the collaborative approach elements, especially at accountability, communication, involvement, and equity to identify elite capture. In the end, the elite capture causes a lack of contribution and cooperation as a group to achieve social forestry program goal.